CRYSTAL STRUCTURE TRANSFORMATION OF Ba-Sr HEXAFERRITE AND ITS EFFECT ON PARTICLE ORIENTATION IN RECYCLE PROCESS - Agus Sukarto Wismogroho; Wahyu Bambang Widayatno; Toto Sudiro; Didik Aryanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
CRYSTAL STRUCTURE TRANSFORMATION OF Ba-Sr HEXAFERRITE AND ITS EFFECT ON PARTICLE ORIENTATION IN RECYCLE PROCESS. In general, during its fabrication, 2-5%of total products of Ba-Sr hexaferrite permanent magnet will be rejected.Accordingly, an increase in rejected product of permanent magnet needs to be considered. It is expected that the re-utilization of rejected product can increase the production efficiency in order to achieve zero waste-production. In the present work, the recycling process of Ba-Sr hexaferrite permanent magnet was studied by applying 1 T magnetic field (anisotropic) to align the powder. The rejected products were milled using shaker mill PPF-UG for 10-40 min and then sintered at 1200 ºC for 60 min. The results show that the remanence of original powder was increased by 50% after the particle orientation. However, the recycled sample doesn’t show a significant different. SEM and XRD analysis show the crystalline structure transformation from symmetrical hexagonal to asymmetrical hexagonal structure with crystalline growth in a-b axis direction. This transformation leads to lost in its magneto crystalline anisotropy. Therefore, it was difficult to align the particle.